'Just be Easy, Feel the Music' – Branding in the Musical and Social Life of Kampala's Hip-hop Scene. Issue 4 (2nd October 2021) - Singh, Simran
ABSTRACT: Situating branding as socio-cultural performative practice, this article provides critical insight into the hip-hop scene in Kampala, Uganda, with spatial contexts evoked through ethnographic accounts. Focusing on a recording studio in the city, branding mobilises, first, musical life through performative practices such as the creation of musical commodities informed by sound and image; and second, branding characterises and extends social life through formal and informal collaborative processes. Sustaining this is hip-hop's prominence as a global brand of popular culture; apprehendings of the genre act in response to problematic social and economic issues in Uganda, engendered in turn by neoliberal structural adjustment policies and development interventions. Drawing on popular music studies and postcolonial scholarship, this article argues that practices of branding in Kampala's hip-hop milieu acts in response to this social and economic uncertainty.